2005
DOI: 10.1523/jneurosci.2678-05.2005
|View full text |Cite
|
Sign up to set email alerts
|

Visual Prey Capture in Larval Zebrafish Is Controlled by Identified Reticulospinal Neurons Downstream of the Tectum

Abstract: Many vertebrates are efficient hunters and recognize their prey by innate neural mechanisms. During prey capture, the internal representation of the prey's location must be constantly updated and made available to premotor neurons that convey the information to spinal motor circuits. We studied the neural substrate of this specialized visuomotor system using high-speed video recordings of larval zebrafish and laser ablations of candidate brain structures. Seven-day-old zebrafish oriented toward, chased, and co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

15
338
0
1

Year Published

2006
2006
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 310 publications
(354 citation statements)
references
References 43 publications
(53 reference statements)
15
338
0
1
Order By: Relevance
“…The retina of Betta splendens was formed (with seven layers) within 4 days and similar reports were observed on zebrafish (Danio rerio) (Gahtan et al, 2005) and catfish (Pangasianodon hypophthalmus) (Mukai et al, 2010). While, Oliveira and Sa (2012) have reported that the eye of B. splendens is strongly pigmented at hatching, other study claim that at this stage the eyes of B. splendens are undifferentiated and only slightly pigmented (Valentin et al, 2013).…”
Section: Discussionsupporting
confidence: 77%
“…The retina of Betta splendens was formed (with seven layers) within 4 days and similar reports were observed on zebrafish (Danio rerio) (Gahtan et al, 2005) and catfish (Pangasianodon hypophthalmus) (Mukai et al, 2010). While, Oliveira and Sa (2012) have reported that the eye of B. splendens is strongly pigmented at hatching, other study claim that at this stage the eyes of B. splendens are undifferentiated and only slightly pigmented (Valentin et al, 2013).…”
Section: Discussionsupporting
confidence: 77%
“…The discrete organization that we see, which differs from previously observed distributed activity 4,18,30 , is made apparent by the ability to evoke simple motor patterns with controlled visual stimulation. The fact that more complex behaviors are associated with distributed activation of many neurons is consistent with a model in which subsets of neurons initiate distinct components of the behavior 31,32 .Additional evidence for a distributed motor command has come from a number of studies that found that ablations do not abolish specific behaviors, although they can alter their latency and kinematics 16,17,[33][34][35] . Here, an ablation guided by an observed functional organization was able to completely abolish a specific behavior; optomotor turns in one direction were specifically eliminated by ablation of the small number of cells responsive to turn-evoking stimuli.…”
mentioning
confidence: 54%
“…Additional evidence for a distributed motor command has come from a number of studies that found that ablations do not abolish specific behaviors, although they can alter their latency and kinematics 16,17,[33][34][35] . Here, an ablation guided by an observed functional organization was able to completely abolish a specific behavior; optomotor turns in one direction were specifically eliminated by ablation of the small number of cells responsive to turn-evoking stimuli.…”
Section: Discussionmentioning
confidence: 99%
“…Subpopulations of RSNs located in discrete brainstem regions are recruited in the control of different components of sensorimotor integration (Dampney, 1994;UllĂ©n et al, 1997;Orlovsky et al, 1999;Fagerstedt et al, 2001;Yeomans et al, 2002;Dubuc et al, 2008). In teleost fish, lesion experiments and imaging of neuronal activity suggest that subpopulations of RSNs in midbrain and hindbrain are important for control of visual prey capture (Gahtan et al, 2005), fast escape (see below), and optomotor response (Orger et al, 2008).…”
Section: Introductionmentioning
confidence: 99%